Individual and Environmental Predictors of Age of First Intercourse and Number of Children by Age 27 - Dragan, Wojciech Ł.; Bates, John E.; Lansford, Jennifer E.; Dodge, Kenneth A.; Pettit, Gregory S. (Frontiers in Psychology, 2020)
Reproductive behavior characteristics may be influenced by both social and individual factors. Recent studies have revealed that personality traits might be related to reproductive characteristics in adulthood. Little is known about potential mediators or moderators of relations between personality and reproductive behavior. The present study examines the relation between personality traits measured in early adolescence and the number of children people have at age 27, with an attempt to identify moderation and mediation effects. We used data from the longitudinal cohort (N=585) collected as a part of the Child Development Project. Personality was measured with the use of Lanthier’s Big Five Personality Questionnaire. Results from regression analyses and structural equation models showed that four of the five personality traits (except extraversion) were related to the number of children individuals had, and these associations were mediated by the age of first intercourse and participants’ familial and educational plans. We also identified moderation effects of IQ and SES both on the associations of personality traits with mediators and the number of children at age 27.